2012
DOI: 10.1007/978-3-642-24186-4_9
|View full text |Cite
|
Sign up to set email alerts
|

Disorder Effects on Exciton–Polariton Condensates

Abstract: SummaryThe impact of a random disorder potential on the dynamical properties of Bose Einstein condensates is a very wide research field. In microcavities, these studies are even more crucial than in the condensates of cold atoms, since random disorder is naturally present in the semiconductor structures. In this chapter, we consider a stable condensate, defined by a chemical potential, propagating in a random disorder potential, like a liquid flowing through a capillary. We analyze the interplay between the ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…This means that the top and bottom surfaces of the as-grown crystal are parallel to each other, and thus the crystals are ideal as the active media with a constant cavity length. The spatial uniformities in the photonic and excitonic potentials are key requirements to avoid polaritonic potential disorder inhibiting the formation of spatial coherence among the polariton particles. , Therefore, we consider that the BP1T-CN single crystal is a very promising material for cavity-polariton studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This means that the top and bottom surfaces of the as-grown crystal are parallel to each other, and thus the crystals are ideal as the active media with a constant cavity length. The spatial uniformities in the photonic and excitonic potentials are key requirements to avoid polaritonic potential disorder inhibiting the formation of spatial coherence among the polariton particles. , Therefore, we consider that the BP1T-CN single crystal is a very promising material for cavity-polariton studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Organics offer the advantage of a broad spectral range beyond that covered by GaN and ZnO and can be easily fabricated without the need for epitaxial growth. As-grown films, however, tend to be highly disordered and to overcome possible localization effects [12][13][14][15][16][17][18][19][20][21][22][23][24], the first demonstration of organic polariton condensation used a single-crystalline organic semiconductor as the active material [1]. Two recent demonstrations, however, have shown that the same phenomenology can be extended to amorphous systems: one consisting of a spin-coated polymer [3] and the other of a thermally evaporated oligomer [2].…”
mentioning
confidence: 99%
“…Here, we do not perform a more detailed study of the features that are specific to the disorder in the polariton systems, e.g. 26, but only use the exponential tails of the correlation function as a characteristic feature of the localization mechanism.…”
Section: Anderson Localizationmentioning
confidence: 99%